The Relationship between Iraqi EFL Teachers’ Professional development and Their Classroom Management - Aliakbari, Mohammad; Hasoon, Alaa Mkhelf (Al-Adab Journal, 2022)
The present study investigated the relationship between Iraqi EFL teachers’ professional development (PD) and their classroom management techniques. The former is a general term that means developing yourself professionally and the latter relates to improving your classroom management abilities by learning new strategies and techniques, motivating students, and having all students practicing by asking questions. The study included participation of 275 EFL teachers of both sexes and different ages. They were chosen according to Krejcie and Morgan's (1970) formula, with a confidence level of 95%. from different language schools. As instruments. the Classroom Management Techniques questionnaire (Diaz, Gonzalez, Ramirez, & Munoz-Parra, 2018) and Teachers’ Professional Development scale (Evers, Kreijns, & Van der Heijden, 2016) were used to collect the required data. The findings made it clear that Classroom management correlated positively and significantly with Professional Development (r=.42, p<.05). The results of the complementary interview phase made it clear that teachers strongly agreed with need for PD programs and thought the higher the level of the teacher's professional activity, the higher the scientific level of the students can be expected.